3 - Slavery as a Human Institution - John Edward Philips, (Afrika Zamani, 2022)
Scholars of slavery have long been divided between those who define slaves primarily as human property and those who define slaves primarily as kinless outsiders. This article reconciles these competing definitions by using the new understanding of definitions popularized by George Lakoff in his book Women, Fire and Dangerous Things. The two formal definitions that have been offered are really two sides of the same coin. Slaves in Africa were property because they were kinless outsiders, while slaves in the United States were kinless out- siders because they were property. Slaves in other societies also had this dual character as both property and kinless outsiders. Slavery is a human institution that began in the psychological dependence caused by the shame of kinlessness experienced by isolated individuals. It was thus a mechanism for the incorpora- tion of new members into a society. It spread and developed in human societies, coming to have various extensions in different societies, but always so recog- nizably similar that slaves could easily be transferred between cultures that had very different understandings of slavery.